2008
DOI: 10.1007/s12052-008-0061-8
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Understanding the Nature of Science for Accepting Evolution

Abstract: Many students reject evolutionary theory, whether or not they adequately understand basic evolutionary concepts. We explore the hypothesis that accepting evolution is related to understanding the nature of science. In particular, students may be more likely to accept evolution if they understand that a scientific theory is provisional but reliable, that scientists employ diverse methods for testing scientific claims, and that relating data to theory can require inference and interpretation. In a study with uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
178
2
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(207 citation statements)
references
References 37 publications
9
178
2
15
Order By: Relevance
“…Though several interesting measurement tools exist (e.g., Rutledge and Warden 1999;Rutledge and Sadler 2007;Aikenhead and Ryan 1992;Siegel and Ranney 2003;Lombrozo et al 2008;Johnson and Peeples 1987;Miller et al 2006), to date, the present survey represents the most comprehensive attempt to incorporate a broad array of explanatory variables of theoretical importance.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Though several interesting measurement tools exist (e.g., Rutledge and Warden 1999;Rutledge and Sadler 2007;Aikenhead and Ryan 1992;Siegel and Ranney 2003;Lombrozo et al 2008;Johnson and Peeples 1987;Miller et al 2006), to date, the present survey represents the most comprehensive attempt to incorporate a broad array of explanatory variables of theoretical importance.…”
Section: The Present Studymentioning
confidence: 99%
“…Exposure to Evolutionary Theory Research has shown that those who seek information about evolutionary theory may in fact know more about it and accordingly hold more positive attitudes (Lombrozo et al 2008). Natural history museums, for example, function in part to teach the public about evolution (Diamond and Evans 2007).…”
Section: Creating the Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…This literature suggests that (a) individuals who seek exposure to evolutionary theory (e.g., in coursework or museum visits) demonstrate greater knowledge and report more positive attitudes toward the theory than those who do not seek exposure (e.g., Lombrozo et al 2008;McFadden et al 2007), (b) religious identity and political ideology enhance or impede the seeking of such knowledge (e.g., genetic literacy; Scott 2004;Miller et al 2006;Paterson and Rossow 1999), and (c) knowledge of scientific epistemology is positively associated with both evolutionary knowledge and attitudes about its relevance (Hawley et al 2011). Until recently, no suitable comprehensive measure existed to assess curricular effectiveness, attitude change, or descriptions of regional populations.…”
mentioning
confidence: 99%
“…À ce titre, les travaux en didactique des SVT menés par Orange-Ravachol (2010) [21] sur la problématisation du temps et son irréversibilité pointent du doigt la nécessité de dépasser le principe explicatif de l'actualisme pour intégrer le principe de contingence historique. D'autres travaux soulignent les limites d'un enseignement uniquement focalisé sur le contenu scientifique, en particulier, quand il s'agit de faire face à la controverse créationnisme versus évolutionnisme (Lombroso, Thanukos et Weisber, 2008;Pigliucci, 2007) [22,23]. Ces travaux témoignent, à des degrés divers, de la difficulté qu'ont les élèves à conjuguer et à naviguer entre l'explication fonctionnaliste et l'explication historique de la diversification du vivant.…”
Section: La Causalité éVolutive Une Composante De La Nature De La Scunclassified